2019
DOI: 10.1002/aqc.3155
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of fish spillover from freshwater protected areas in lakes of eastern Ontario

Abstract: Research has identified numerous conservation benefits attributed to the use of marine protected areas (MPAs), yet comparatively less is known about the effectiveness of freshwater protected areas (FPAs). This study assessed multiple long‐standing (>70 years active) intra‐lake FPAs in three lakes in eastern Ontario, Canada, to evaluate their potential conservation benefits. These FPAs were intended initially to protect exploited populations of largemouth bass (Micropterus salmoides (Lacépède, 1802)), but since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 76 publications
(124 reference statements)
0
21
0
1
Order By: Relevance
“…; Zolderdo et al. ). Although, this seems unlikely given that the relatively large Bluegill that were used in this experiment (~13 cm TL) are generally free from predation by aquatic piscivores (mainly Largemouth Bass) and prior work has demonstrated a size‐dependent perception of risk in sunfishes (Werner et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Zolderdo et al. ). Although, this seems unlikely given that the relatively large Bluegill that were used in this experiment (~13 cm TL) are generally free from predation by aquatic piscivores (mainly Largemouth Bass) and prior work has demonstrated a size‐dependent perception of risk in sunfishes (Werner et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as CPUE is often considered a factor of abundance (Hinton and Maunder 2003; Haggarty and King ; Tsuboi and Endou ) and that both abundance and biomass of Bluegill is comparable across our study regions in this particular lake (Zolderdo et al. ), we might not have expected any significant influence of the APA on CPUE in this study. Nonetheless, we urge caution when interpreting these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodiversity conservation that is linked to livelihoods of local communities is explored in large provinces such as the Andes (Tognelli et al, ), the Amazon (Reis et al, ) and Lake Victoria (van Soesbergen, Sassen, Kimsey & Hill, ). Water planning that includes life‐history needs of specific species is described in the Columbia River Basin of the USA (coho salmon; Flitcroft et al, ) and in discrete systems such as the Hunter Valley in Australia (Linke, Turak, Gulbrandsen Asmyhr, & Hose, ), Greek lakes (Stefanidis, Sarika, & Papastergiadou, ) and Lake Ontario (North America) (Zolderdo et al, ). Taken together, these manuscripts are intended to convey the scope and complexity of freshwater conservation in this time of global transformation, as systems from the atmosphere to the Earth's crust adjust to vast human‐derived change.…”
Section: Invigorating Freshwater Conservation Approachesmentioning
confidence: 99%
“…Their study indicates that there are often many more freshwater areas that need to be protected than are manageable; nevertheless, it is important to identify priority areas for conservation action that provide networks of freshwater conservation with connection between them. Tognelli et al () and Zolderdo et al () highlight how these protected areas can act as refugia for species, which may then move out to populate areas nearby and so provide regional benefits. Both Tognelli et al () and Linke, Hermoso, and Januchowski‐Hartley () found that expanding the species of interest increased the area that needed to be considered for conservation, but there was significant overlap in prioritized locations.…”
Section: Protecting Species and Habitatsmentioning
confidence: 99%